2006
DOI: 10.1103/physrevlett.96.186104
|View full text |Cite
|
Sign up to set email alerts
|

C60Molecular Bearings and the Phenomenon of Nanomapping

Abstract: Inspired by suggestions of C(60) "nanobearings," we have measured sliding friction on fixed and rotating C(60) layers to explore whether a lubricating effect is present. We refer to this general phenomenon as "nanomapping," whereby macroscopic attributes are mapped in a one on one fashion to nanoscale entities. Our measurements are the first to directly link friction to a documented molecular rotation state. Friction is, however, observed to be higher for rotating layers, in defiance of the ball-bearing analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…6(b)) between the surfaces in order to reduce friction. Experimental studies have suggested that unlike macroscopic systems, there is little (if any) benefit of the rolling action for nanoparticles compared to sliding [258,259]. Hard nanoparticles may also reduce friction through polishing ( Fig.…”
Section: Nanoparticle Friction Modifiersmentioning
confidence: 99%
“…6(b)) between the surfaces in order to reduce friction. Experimental studies have suggested that unlike macroscopic systems, there is little (if any) benefit of the rolling action for nanoparticles compared to sliding [258,259]. Hard nanoparticles may also reduce friction through polishing ( Fig.…”
Section: Nanoparticle Friction Modifiersmentioning
confidence: 99%
“…It is unclear whether nanoparticles are able to act as nanoscale ball bearings, i.e. if nanoparticle rolling resistance reduces energy losses relative to sliding friction, as is the case for most macroscopic systems [7,8]. Hard nanoparticles may also reduce friction through polishing (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Although C 60 fullerene additives have been shown to reduce friction and wear under specific conditions [3][4][5][6], their action as molecular ball bearings has been widely disputed [7,8] and their overall performance as potential lubricant additives has been somewhat disappointing [1,7,8]. However, larger carbon nanoparticle additives have shown more promise with regard to boundary friction and wear reduction, specifically carbon nanodiamonds (CND) and carbon nanoonions (CNO) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, the higher friction for particles' sliding when compared to rolling at atomic scale matches the common results at the macroscale, which, however, seems to be challenged at some specific microscale. Coffey and Krim utilized quartz crystal microbalance to measure friction levels for molecularly thin methanol films sliding along C 60 substrates in rapid and repressed rotational states, and they observed an increased friction for the case of rapid rotation C 60 [45]. Thereafter, Braun and Tosatti indicated that rolling spherical lubricant molecules can indeed provide better tribological parameters than sliding atomic lubricants, however, it is as large as in macroscopic friction only for a low concentration of lubricant molecules, and for special systems and friction conditions [46].…”
Section: Movement Pattern Of Abrasive Particlementioning
confidence: 99%
“…By comparing these results, one needs to carefully check the ingredients of the macroscale and nanoscale systems before making the claim whether the rolling benefits the friction reduction. [45]. Thereafter, Braun and Tosatti indicated that rolling spherical lubricant molecules can indeed provide better tribological parameters than sliding atomic lubricants, however, it is as large as in macroscopic friction only for a low concentration of lubricant molecules, and for special systems and friction conditions [46].…”
Section: Movement Pattern Of Abrasive Particlementioning
confidence: 99%